Homoeopathy as a First-Line Treatment: An Emerging Paradigm in Healthcare (Homoeopathy for All, 2024)
Homoeopathy, a system of  alternative medicine founded by  Samuel Hahnemann in the late  18th century, is gaining traction as  a viable first-line treatment option  worldwide. This article examines  the foundational principles, clinical  efficacy, and increasing acceptance  of homoeopathy within modern  healthcare, especially in primary  care contexts.
Keywords: minimizing toxicity; Clinical Efficacy; scientific